Effects of head movement and proprioceptive feedback in training of sound localization - Honda, Akio (Pion, 2013)
We investigated the effects of listeners' head movements and proprioceptive feedback during sound localization practice on the subsequent accuracy of sound localization performance. The effects were examined under both restricted and unrestricted head movement conditions in the practice stage. In both cases, the participants were divided into two groups: a feedback group performed a sound localization drill with accurate proprioceptive feedback; a control group conducted it without the feedback. Results showed that (1) sound localization practice, while allowing for free head movement, led to improvement in sound localization performance and decreased actual angular errors along the horizontal plane, and that (2) proprioceptive feedback during practice decreased actual angular errors in the vertical plane. Our findings suggest that unrestricted head movement and proprioceptive feedback during sound localization training enhance perceptual motor learning by enabling listeners to use variable auditory cues and proprioceptive information.